Ranpo par inflexion ou Nagoya en mutation, recension de Ranpo et Nagoya : modernisme d’une ville de province et paysage originel du roman policier, de Komatsu Shōko - Hirotaka Ichiyanagi (Ebisu: Études Japonaises)
An analysis of Ranpo and Nagoya: Local City Modernism and the Original Landscape of Detective Stories, by Komatsu Shōko. Ranpo spent most of his childhood in Nagoya. How did the modernist urban culture of the late Meiji era, with its mix of conservatism and progressivism, influence Ranpo’s sensibility as an author? This book examines the trends in mystery novels revolving around the person of Ranpo.